Investigation on removal of damaged Aluminium honeycomb secondary bonded to the Glass Fibre Reinforced Polymer (GFRP) composite laminate through milling and grinding operation - Ahmad Naufal Abdul Rahman (Nanyang Technological University, 2020)
The objective of this Final Year Project (FYP) is to suggest a possible percentage of sodium hydroxide needed to remove the adhesive bond of a composite sandwich structure comprising of an aluminium honeycomb core adhesively bonded to carbon-fibre reinforced polymer (CFRP) substrates. The current practice is to perform base etching which is has a high efficiency and effectiveness at removing the adhesive bond from the composite structure. However, using an alkaline solution, NaOH, increases the degradation effect on the composite properties, particularly flexural properties. Three possible concentrations, 5%, 10% and 20% were evaluated to determine their efficiency and effectiveness as well as the extent of degradation effect on the composite structure. The ASTM D790 standards and the flexural strength and strain were being compared and studied. Water immersion tests were done to determine whether there is more weight gain from water when exposed to different concentrations of NaOH. 3-point bending tests were done next, to examine the specimens’ failure mode at different point phase of load stress drop. In order to examine failures due to delamination or transverse crack, an optical microscope was used. To determine any decrease in flexural strength and strain, specimen data was compared with the control data.